Evaluation of The Success of The Implementation of PT XYZ’s Vendor Invoicing Portal (VIP) System Using Delone & Mclean’s Information System Success Model - Fitriyah, Lailatul (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to evaluate the success of the VIP system implementation using the Information System Success Model by DeLone and McLean, by adding the variables of trust and perceived risk to enrich the evaluation model in the context of digital transaction systems. The research model includes eight main constructs: system quality, information quality, service quality, perceived risk, trust, intention to use, user satisfaction, and net benefit. This research used a quantitative approach with a questionnaire instrument distributed to internal and external users of the VIP system. Data analysis is conducted using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The research results show that trust has a significant effect on the intention to use, while system quality, information quality, service quality, and perceived risk do not have a significant effect on the intention to use. These findings indicate that in systems that are mandatory or required as part of a company’s business process, trust in the security and reliability of the system becomes the main factor driving usage. Service quality significantly affects user satisfaction, while intention to use and user satisfaction significantly affect net benefit. These results indicate that the benefits of the VIP system are primarily obtained thru a positive user experience and a high level of user satisfaction. This research provides empirical contributions to the development of information system success models in the context of digital payment systems and offers strategic recommendations for improving service quality and the effectiveness of VIP system implementation at PT XYZ.